Determinants of Muslim Taxpayer Compliance: The Moderating Role of Religiosity and the Integration of Zakat Knowledge - Muhammad Andri Ashari; Dewi Susilowati (Universitas Muhammadiyah Makassar, 2026)
Taxpayer compliance remains a persistent challenge in Indonesia, particularly among Muslim taxpayers whose fiscal responsibilities coexist with religious obligations such as zakat. While prior studies have emphasized economic and administrative determinants, limited attention has been given to the integration of religious dimensions within a comprehensive compliance framework. This study aims to examine the effects of tax socialization, taxpayer awareness, tax sanctions, and zakat knowledge on taxpayer compliance, with religiosity positioned as both a direct determinant and a moderating variable. This study employs a quantitative explanatory approach using primary data collected from 120 registered Muslim individual taxpayers in Cilacap Regency, Indonesia, through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct and interaction effects among variables. The findings reveal that tax socialization, taxpayer awareness, tax sanctions, and zakat knowledge have positive and statistically significant effects on taxpayer compliance, with zakat knowledge emerging as the strongest predictor. Religiosity not only directly enhances compliance but also significantly strengthens the relationships between all key determinants and compliance behavior. These results indicate that compliance is shaped by the interaction between institutional mechanisms and internal moral–religious values. This study contributes to the tax compliance literature by proposing an integrative framework that incorporates zakat knowledge and religiosity within Attribution Theory. The findings provide practical implications for policymakers to design culturally and religiously aligned tax policies, emphasizing the importance of combining enforcement strategies with value-based approaches to enhance voluntary compliance in Muslim-majority contexts.